Crystal chemistry and photomechanical behavior of 3, 4-dimethoxycinnamic acid: correlation between maximum yield in the solid-state topochemical reaction and cooperative molecular motion. (2015) - Mishra, Manish Kumar; Mukherjee, Arijit; Ramamurty, Upadrasta; Desiraju, Gautam R.
No abstract available